A terapia comunitária integrativa e a enfermagem : revisão integrativa de literatura - Santos, Mallu Gabriele dos (2019)
With social movements, the Psychiatric Reform, and the creation of the Unified Health System (UHS), there was the consolidation of the rights of users in psychological distress. In 2008 the Ministry of Health instituted the National Policy for Integrative Practices in Mental Health, recognizing Integrative Community Therapy (ICT), created by Adalberto Barreto, as one such practice. The present study aimed to gather and identify the evidence available in the scientific literature about ICT as a nursing care practice, thus producing an Integrative Literature Review, which followed the PRISMA recommendations for research and selection of articles for analysis. The methodological approach chosen was exploratory and descriptive, by qualitative research. The study were categorized through thematic analysis, resulting in five thematic axes: What is Integrative Community Therapy?; Who are the community therapists? The TCI method (step by step); Nursing and ICT; TCI's contributions to those involved. The results indicate that the ICT constitutes a space of welcome and listening, which provides the involved improvements such as increased self-esteem, self-knowledge, and overcoming daily problems. In Primary Care it has proved to be an important tool for bringing health professionals closer to users, enabling and strengthening actions for the promotion and prevention of mental health (MH). Nurses showed significant participation in the training of community therapists, and in the implementation of ICT as care in MH at different levels of care, with varied public. It has also been shown that nursing has the most number of scientific publications in the area. It is concluded that ICT is a light-weight care technology, contrary to most studies that classify it as a light technology without considering Merhy's definitions of care technology; and that is in line with SUS guidelines and integrative practices policies. It is characterized as a care action that promotes changes in the quality of health care, the strengthening of communities, and the recovery of people in psychological distress. However, currently there is a tendency to get back mental health care asylum in Brazil. The Technical Note 11/2019, which provides clarification on changes in the National Mental Health Policy and the National Drug Policy Guidelines, threatens the rights gained as they bring back Psychiatric Hospitals and compulsory hospitalization, thus contrary to the global trends in care in MH and the guiding and organizational principles of UHS. Nursing, which has been evidenced as a strengthening category of integrative care practices, should not omit from this setback and organize itself for the struggle in defense of the rights conquered by the Brazilian people.